Preparation of CuInSe2 Thin Films by using Various Methods (A Short Review) - Ho, Soon Min; Sreekanth, Mandati; Ramkumar, Chandran; Archana, Mallik; Mohammad Arif Sobhan, Bhuiyan; Deepa, K.G. (2019)
CuInSe2 thin films are very important semiconductor material for solar cell applications because of chemical stability, direct band gap and high optical absorption coefficient. In this work, a review of CuInSe2 fils prepared using different deposition techniques such as electrodeposition, solvothermal, vacuum evaporation, hydrothermal and pulsed electrodeposition technique is presented. The review also includes the study of physical properties of these films which were derived using the characterization techniques such as field emission scanning electron microscopy, X-ray diffraction, Energy dispersive X-ray analysis, atomic force microscopy, UV-VIsible spectrophotometer and Raman spectroscopy.